PENGGUNAAN AQUAFABA KACANG ARAB SEBAGAI ALTERNATIF PENGGANTI PUTIH TELUR DALAM PEMBUATAN MACARON - Astiana, Rachmat; Ihsan, Naufal; Puspita Rini, Rosie Oktavia (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2023)
Macaron is an Italian pastry made from almond flour, sugar and egg whites. This research was developed to use chickpea aquafaba as a substitute for egg whites in macaron. This research was conducted as a way to find alternatives for those who have allergies or vegetarians, vegans and lacto vegetarians, to be able to consume macaron products. The method used was an experiment with organoleptic tests on 33 trained and untrained panelists as respondents. The results of this study indicate that the texture of aquafaba macaron is not as crunchy as using egg white, in terms of taste it is not too sweet and a little savory, the color is duller and paler, and has a stronger peanut aroma, but overall the use of chickpea aquafaba can approach the characteristics of macaron using eggs.